An Earth‐Abundant Ni‐Based Single‐Atom Catalyst for Selective Photodegradation of Pollutants. Issue 7 (9th July 2021) - Vilé, Gianvito; Sharma, Priti; Nachtegaal, Maarten; Tollini, Flavio; Moscatelli, Davide; Sroka-Bartnicka, Anna; Tomanec, Ondrej; Petr, Martin; Filip, Jan; Pieta, Izabela S.; Zbořil, Radek; Gawande, Manoj B.
Abstract : Photodegradation of Pollutants In article number 2100176, Gianvito Vilé, Manoj B. Gawande, and co‐workers disclose how ligand‐metal charge transfer effects in single‐atom catalysts can be exploited to degrade water pollutants under visible light conditions, demonstrating a decreased formation of toxic fragmentation byproducts and an enhanced selectivity to CO2 . This opens new opportunities for the rational design of improved single‐atom photocatalysts for clean water applications.